2020
DOI: 10.14740/jmc3515
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic Lymphohistiocytosis in a Patient With Acute Respiratory Distress Syndrome Secondary to SARS-CoV-2 Infection

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a potentially lifethreatening entity resulting from the dysregulated activation of Tlymphocytes. Secondary HLH (sHLH) complicates various medical conditions. Similar to 2009 H1N1 influenza, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection appears to trigger a cytokine storm in a subset of individuals. The patient of 64 years old presented himself in the emergency department with cough and fever, and was subjected to the nasopharyngeal swab and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The utility of the H-score in the COVID-19 setting has been controversial. Some studies suggest the utilization of the H-score as diagnostic criteria for sHLH in CO-VID-19 patients, while some studies propose H-score as a tool for predicting the outcome of COVID-19 patients [16][17][18]. Organomegaly, hypofibrinogenemia, and cytopenia are common features among HLH patients, while COVID-19 patients mostly present with hyperfibrinogenemia, leukocytosis, and no sign of organomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of the H-score in the COVID-19 setting has been controversial. Some studies suggest the utilization of the H-score as diagnostic criteria for sHLH in CO-VID-19 patients, while some studies propose H-score as a tool for predicting the outcome of COVID-19 patients [16][17][18]. Organomegaly, hypofibrinogenemia, and cytopenia are common features among HLH patients, while COVID-19 patients mostly present with hyperfibrinogenemia, leukocytosis, and no sign of organomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Children reported with COVID-19 were classified into one of the following categories: 7 • Asymptomatic infection: without any clinical symptoms and signs Table 2. Clinical characteristics of the study population This study highlighted that majority of paediatric patients diagnosed with COVID-19 were identified through contact investigation or community tracing.…”
Section: Methodsmentioning
confidence: 99%
“…9 Cytopenia, lymphopenia, and HLH associations have been reported with coronavirus infection in adults. 7,[10][11][12] However, there has been no such association of "neonatal 1). Cytokine release syndrome refers to a form of systemic inflammatory response syndrome (SIRS) that can be triggered by infections or certain drugs.…”
mentioning
confidence: 99%
“…The second controversy is whether coronavirus infection can trigger onset of cytopenia and hemophagocytosis associated with familial HLH and UNC13D mutations 9 . Cytopenia, lymphopenia, and HLH associations have been reported with coronavirus infection in adults 7,10–12 . However, there has been no such association of “neonatal COVID” and “familial HLH” reported for “COVID hemophagocytosis syndrome” or “COVID HLH syndrome.”…”
mentioning
confidence: 99%